COMPETENCY BASED OR COMPETENCY DRIVEN MEDICAL EDUCATION IN FORENSIC MEDICINE: CROSSROADS AND WAY FORWARDS (Journal of Forensic Medicine & Toxicology, 2022)
Health care systems all over the world are transforming to align with the needs of 21st century patients and community at large. Also, there is great need of transformation in the educational systems that prepare the health care professionals who deliver care with compassion and treat the patient as whole, not just the disease.1-3 The world over, a paradigm shifts toward competency based medical education - a comprehensive educational strategy is widely approaching.4-6 Flexner report stated that most of curriculum is delivered in “Flexnerian” fashion which directly means that medical school focused upon the factual basic science disciplines in silos.7 After many years in the making, an increasing number of postgraduate medical education (PGME) training programs in India are now adopting a competency-based medical education (CBME) framework based on Entrustable Professional Activities (EPAs) that, in turn, encompass a larger number of competencies and training milestone. After successfully implementation in postgraduate medical education, CBME is now being incorporated into undergraduate medical education (UGME) intended to improve integration across the medical education continuum and to facilitate a smooth transition from clerkship to residency by ensuring that all graduates are ready for indirect supervision of required EPAs.
Keywords: teaching-learning; strategies; graduates